2007
DOI: 10.1128/mcb.01615-07
|View full text |Cite
|
Sign up to set email alerts
|

T-bet's Ability To Regulate Individual Target Genes Requires the Conserved T-Box Domain To Recruit Histone Methyltransferase Activity and a Separate Family Member-Specific Transactivation Domain

Abstract: Appropriate cellular differentiation and specification rely upon the ability of key developmental transcription factors to precisely establish gene expression patterns. These transcription factors often regulate epigenetic events. However, it has been unclear whether this is the only role that they play in functionally regulating developmental gene expression pathways or whether they also participate in downstream transactivation events at the same promoter. The T-box transcription factor family is important i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
96
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(103 citation statements)
references
References 40 publications
3
96
0
1
Order By: Relevance
“…Based on observations in T-bet-deficient mice and transfected cell lines that T-bet is an absolute requirement for the induction of transcription of CXCR3 and IFN-c in Th1 cells [5][6][7], we proposed that T-bet may also modulate CXCR3 and IFN-c gene expression in sarcoidosis. The T-bet control of CXCR3 expression is of particular interest in sarcoidosis because this chemokine receptor plays a pivotal role in recruiting T-cells to the lungs with subsequent granuloma formation [4].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on observations in T-bet-deficient mice and transfected cell lines that T-bet is an absolute requirement for the induction of transcription of CXCR3 and IFN-c in Th1 cells [5][6][7], we proposed that T-bet may also modulate CXCR3 and IFN-c gene expression in sarcoidosis. The T-bet control of CXCR3 expression is of particular interest in sarcoidosis because this chemokine receptor plays a pivotal role in recruiting T-cells to the lungs with subsequent granuloma formation [4].…”
Section: Discussionmentioning
confidence: 99%
“…In view of the crucial role of T-bet in Th1 differentiation [8] and its requirement for CXCR3 and IFN-c upregulation [5][6][7], we hypothesised that T-bet is involved in the pathogenesis of the Th1-polarised inflammation in sarcoidosis. In line with this hypothesis, our data showed that T-bet mRNA expression is elevated in sarcoidosis patients when compared to control subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A structure-function analysis revealed that separable chromatin remodeling and transactivation activities are needed for T-bet to activate target promoters. Interestingly, the transactivation potential localized to the Nand C-terminal regions of the protein, while the ability to recruit a permissive histone H3 Lys 4 dimethyl (H3K4me2)-specific methyltransferase complex localized to the T-box DNA-binding domain (Lewis et al 2007). …”
mentioning
confidence: 99%
“…20 Importantly, recent work has shown that both the removal of the H3K27me3 modification and the addition of the H3K4me2 mark at the Ifng promoter are dependent upon T-bet. 24,25 The mechanism by which T-bet induces these epigenetic changes during Th1 differentiation appears to be through a physical interaction with the H3K27-demethylase JMJD3 and the H3K4-methyltransferase Set7/9, with the interaction interfaces localizing to separable, but overlapping contact points in the T-box DNA binding domain. 25 Point mutations in the T-box domain that disrupt T-bet's ability to associate with these enzymatic complexes are completely deficient in their ability to activate endogenous T-bet target gene expression revealing the functional importance for the interactions.…”
Section: T-bet Physically and Functionally Interacts With H3k27-demetmentioning
confidence: 99%